Reflection and Learning From the 2019 General Election and the 2020 Regional Election: An Analysis of The Election Implementation Experience in Indonesia - Habibi, Muhammad; Destavino, Irvanus; Mahadika, Alam (Kybernology : Journal of Government Studies, 2023)
This study aims to examine various aspects of elections in Indonesia, encompassing electoral design, the application of information technology, budget allocation, and various issues in the 2019 General Election and the 2020 Election, with the objective of reflecting and evaluating the implementation of the 2024 General Election. The research was conducted using a qualitative approach and descriptive analysis, where primary data were collected through in-depth interviews with stakeholders involved in the general elections and regional elections, as well as through observations and documentation studies. The results indicate that a lack of focus on law enforcement aspects during the legislative process is the primary cause of these issues. Furthermore, several norms were identified as being less practical when applied in the field. These findings underscore the need for clarification and harmonization in Indonesia's election legislation.